Research and development on antidiabetic herbs : Malaysia perspective - Kasmuri, Abdul Razak (IIUM Press, 2011)
Malaysian market value for herbal industry was estimated to grow at 10% annually and the total market value of Malaysian herbal industry in 1999 was RM 4.55 billion (Huda et aI., 2007; Zainal, 2007). On the other hands, diabetes mellitus (DM) is a major and growing health problem since it is the fourth or fifth leading cause of death in most developed countries (Shafie et aI., 2004). In Malaysia, National Health and Morbidity study showed that there was an increase in the prevalence of DM among adults above 30 years old of Peninsular Malaysia from 6.3% in 1986 to 8.8% in 1996 (Chua, 2001). It causes substantial amount of disability, premature mortality, lost of productivity and increased burden on health care budget and facilities